Prevalence of osteoarthritis and clinical outcomes in patients with fractures of the tibial plateau - medium- and long-term analysis - Jon Klasér; Lisa Kotake; Marcus Lindberg; Simon Wigge; Robert Lundqvist; Grzegorz Szczęsny; Przemysław T. Paradowski (BMC Musculoskeletal Disorders)
Abstract Background The incidence of post-traumatic osteoarthritis (OA) following intraarticular knee fractures has been estimated to be relatively high but it varies substantially between different reports. In this study we sought to assess the prevalence of radiographic knee OA secondary to tibial plateau fractures (TPF). The second aim was to report medium- and long-term functional outcomes and investigate whether there were any risk factors associated with these outcomes. Methods We retrospectively reviewed documentation of patients who had TPF between 2001 and 2015. The radiographs, clinical characteristics and patient-reported outcome measures (PROMs) scores were evaluated. Presence of radiographic OA was the primary endpoint. The other endpoints were the relationship between OA and different potential predictors as well as the scores in PROMs. Results The study involved a total of 130 patients including 114 who were radiographically examined at mean follow-up time of 10 years (range 4.6–19.3 years). Radiographic OA was present in 50% of patients (34% in the injured knee and 16% in both knees). Having OA in the contralateral knee increased the odds to develop OA in the index knee (OR = 4.8; 95%CI 1.6–4.1 in the crude model and OR = 6.6; 95%CI 1.8–23.5 in the model adjusted for age, sex, BMI, fracture type and treatment method). The occurrence of OA was associated stronger with medial or bicondylar TPF than with lateral condyle TPF (OR = 2.8; 95%CI 1.2–6.1 in the crude model and OR = 3.4; 95%CI 1.4–8.6 in the adjusted model). The KOOS scores were significantly lower in patients with OA than in those without OA in the index knee in all the KOOS subscales (p < 0.007), except for the KOOS Symptoms (p = 0.362). The EQ-5D-5L index score was significantly higher in patients without OA in the index knee compared to those with OA (p = 0.015). Conclusion Radiographic OA following TPF occurred in 50% of knee joints. The odds for knee OA were highest after medial or bicondylar fractures. Patients with OA in the index knee had lower scores in both condition-specific and generic PROMs than subjects without OA, which indicates that TPF may contribute to the development of both OA disease and illness. Trial registration The trial was registered retrospectively on June 4, 2024 on ClinicalTrials.gov (registration number: NCT06451510).